2021
DOI: 10.1111/jdv.16926
|View full text |Cite
|
Sign up to set email alerts
|

EuroGuiDerm Guideline on the systemic treatment of Psoriasis vulgaris – Part 2: specific clinical and comorbid situations

Abstract: This evidence‐ and consensus‐based guideline on the treatment of psoriasis vulgaris was developed following the EuroGuiDerm Guideline and Consensus Statement Development Manual. The second part of the guideline provides guidance for specific clinical and comorbid situations such as treating psoriasis vulgaris patient with concomitant psoriatic arthritis, concomitant inflammatory bowel disease, a history of malignancies or a history of depression or suicidal ideation. It further holds recommendations for concom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
157
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(168 citation statements)
references
References 299 publications
0
157
0
11
Order By: Relevance
“…Furthermore, some systemic psoriasis therapies are contraindicated during pregnancy owing to their teratogenicity (methotrexate and acitretin) 46 , 47 and others recommended to be used with caution 48 owing to transplacental transfer after the 20th week of gestation (biologics, with the exception of certolizumab pegol) and potential risk of adverse neonatal adverse events 49 , 50 (Supplementary Table IV, available via Mendeley at https://doi.org/10.17632/ccznnnzktg.1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some systemic psoriasis therapies are contraindicated during pregnancy owing to their teratogenicity (methotrexate and acitretin) 46 , 47 and others recommended to be used with caution 48 owing to transplacental transfer after the 20th week of gestation (biologics, with the exception of certolizumab pegol) and potential risk of adverse neonatal adverse events 49 , 50 (Supplementary Table IV, available via Mendeley at https://doi.org/10.17632/ccznnnzktg.1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consecutive adult patients with moderate-to-severe psoriasis unresponsive to topical treatment, phototherapy and/or conventional treatments for psoriasis, undergoing DMF treatment according to the National and International Guidelines [ 15 ], starting treatment from January to September 2020, were included in the study. Patients had to be treated with DMF as monotherapy, as reported in the summary of product characteristics (SPCs), and followed for an observation period of 48 weeks [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Several clinical randomized and observational studies have demonstrated that DMF, among oral traditional systemic agents, presents clinical long-term efficacy and favorable safety profile [ 1 – 3 , 5 ]. A recent European Expert Consensus proposed DMF as a first-line therapeutic option to achieve sustained disease control for patients with moderate-to-severe plaque psoriasis when psoriasis cannot be adequately controlled with topical treatments and phototherapy [ 3 , 10 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The internet portal www.embryotox.de was accessed on 10.12.2021. Preparation Summary of Product Characteristics Website www.embryotox.de National Guidelines [96] International Guidelines [64] and [141] Data on exposure during pregnancy and lactation in humans…”
Section: Ciclosporinmentioning
confidence: 99%